2015
DOI: 10.3390/jmse3020382
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Survey of a Marine Food Fish: Asian Seabass (Lates calcarifer)

Abstract: The Asian seabass (or barramundi; Lates calcarifer) is a marine teleost and a popular food fish in Southeast Asia and Australia. To date, comprehensive genome and OPEN ACCESS J. Mar. Sci. Eng. 2015, 3 383 transcriptome sequence information has not been available for this species in public repositories. Here, we report a comprehensive de novo transcriptome assembly of the Asian seabass. These data will be useful for the development of molecular tools for use in aquaculture of Asian seabass as well as a resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Earlier, transcriptome sequence data was obtained from multiple platforms and assembled into 267,616 contigs [ 16 ]. The scaffolded genome assembly (v2) was obtained using the transcriptome [ 17 ] and yielded 3,807 genomic contigs resulting in a ~10% improvement in N50 metrics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, transcriptome sequence data was obtained from multiple platforms and assembled into 267,616 contigs [ 16 ]. The scaffolded genome assembly (v2) was obtained using the transcriptome [ 17 ] and yielded 3,807 genomic contigs resulting in a ~10% improvement in N50 metrics.…”
Section: Resultsmentioning
confidence: 99%
“…The assembled seabass transcriptome [ 16 ] was used for scaffolding the 90X PacBio genome assembly using the L_RNA_scaffolder tool [ 17 ] ( S1 Table ) resulting in the scaffolded genome assembly (v2).…”
Section: Methodsmentioning
confidence: 99%
“…Whether promoter methylation of dmrt1 (and nr5a2 ) and demethylation of cyp19a1 (and amh ) during barramundi sex inversion is a progressive phenomenon like it has previously been reported for the protogynous ricefield eel [ 16 ] and for the protandrous black porgy [ 17 ], still remains to be elucidated. Nevertheless, this report contributes to the recent body of work aiming to elucidate the genetic mechanisms regulating key reproductive genes involved within the gonads of the large protandrous hermaphrodite barramundi [ 23 , 33 ] and for the first time provides evidence for epigenetics and alternative splicing affecting genes central to sex differentiation pathways in this important aquaculture species.…”
Section: Discussionmentioning
confidence: 91%
“…Results from RT-qPCR revealed that dmrt1 expression was on average 1.9 times higher in the testis than in ovaries, whereas no sex-specific differences were found for cyp19a1 ( Fig 3 ). Further investigation using a publicly available [ 33 ] L . calcarifer RNASeq library of one testes and one ovary (NCBI SRA accessions SRX867251 and SRX867252), whereby raw reads were mapped back to L .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in our present study, three commercially available pelleted grow-out feeds (Feed B-D) and frozen baitfish (Feed A as control) were evaluated based on the overall growth performance, nutritional quality of fillets and histological changes of the mid-gut and liver in juvenile Asian seabass. These data allow us to glimpse into the effects of different feeds onto the gene expression profile of the liver and with the recent availability of the Asian seabass transcriptome [ 29 ], its draft genome [ 30 ] and a comprehensive Asian seabass genome assembly [ 31 ] more detailed analysis of such datasets will be possible in the near future.…”
Section: Introductionmentioning
confidence: 99%